Complex ecological estimation of natural and manmade complexes which basis on MIPS- and risk analysis - Козуля, Тетяна Володимирівна; Ємельянова, Дар’я Ігорівна; Козуля, Марія Михайлівна (Eastern-European Journal of Enterprise Technologies, 2014)
The article provides an algorithmic support which determines the ecological level of systems of natural environment and processes in it. The given algorithmic support allows identifying negative factors disturbing the homeostasis of man-made complexes, and provides complex ecological quality assessment of man-made objects. Using the proposed algorithm of the quality assessment of a complicated system-systematic formation based on MIPS-numbers, risk-characteristic as to the conditions of objects and processes connected with ecological state disturbance, we have received a complex assessment of the studied territory (hard domestic waste landfill (HDWL) in Kharkiv region (the town of Dergachi) and Rivne city(Ukraine), with the pressure indices and ecological security destabilization processes being estimated. The calculations at the given territories have shown the following results: by the activity of chemical influence on the water systems according to the standards of conditions, the environmental risk on Dergachi and Rivne HDWL was determined as acceptable; chlorides were recognised as a destabilizing factor. The investigation involving the complex ecological assessment methodology on the level of system objects allows taking into account the transformation processes of ecological safety destabilization when determining the situation safety level based on the results of monitoring the balance violation factors, which gives the grounds for creating a complex mechanism for quality management of anthropogenic territories.